Business Strategy Formulation for PT Ardhia Multi Parama - Pratama, Teddy Apriliandi; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2013)
The business situation of digital  video-audio industry  will  be  analyzed  from  the  data  that  already collected from observation, interview, and library studies to determine the opportunity in this industry still exist or not. Some analyzing of the internal-external company is the second phase after analyze the business situation, it’s done  to  get  some  information  about  how  strong  the company   to   compete   with   other   competitors.   The analyzing are using Porter five force’s, SWOT analysis, and value chain analysis.  So the business issue of the company is how to win the competition with the current condition. After analyzing all of the situation of the company, the writer  determine  what  kind  of   strategy  to  use  by formulating   the   strategy   using   SWOT   Matrix   and Business Model  canvas. The recommendeation for the company is  to use differentiation strategy because the result  after analyzing the company have strong internal condition, but there are some threats from the  external. So the business issue of the company is how to win the competition with the current condition. Strategy Implementation involves establishing programs to create a series of new organizational activities, budgets to allocate funds to the new activities, and procedures to handle the day-to-day details. With the commitment from all  of  the   employees  in  implementing  the  proposed program, it can be expected can be sustain and grow to be   one   of   the   most   famous   production   house   in Indonesia. Keywords : Digital Video-Audio, Production House